1999
DOI: 10.1098/rspb.1999.0607
|View full text |Cite
|
Sign up to set email alerts
|

Good-genes effects in sexual selection

Abstract: The magnitude of the e¡ect of good genes as a viability bene¢t accruing to choosy females remains a controversial theoretical and empirical issue. We collected all available data from the literature to estimate the magnitude of good-genes viability e¡ects, while adjusting for sample size. The average correlation coe¤cient between male traits and o¡spring survival in 22 studies was 0.122, which di¡ered highly signi¢cantly from zero. This implies that male characters chosen by females reveal on average 1.5% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
406
9
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(426 citation statements)
references
References 19 publications
9
406
9
2
Order By: Relevance
“…Thus, we assume that a male's 'good genes' are 'revealed' in the trait and the female subjects use that information to select the best male. This assumption is supported by the literature on 'good genes' effects in sexual selection (M ller and Alatalo, 1999) and by the demonstration that sexual traits can reveal genetic quality (David et al, 2000;Hale et al, ms). It is also consistent with other sexual selection models (Kokko et al, 2002).…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, we assume that a male's 'good genes' are 'revealed' in the trait and the female subjects use that information to select the best male. This assumption is supported by the literature on 'good genes' effects in sexual selection (M ller and Alatalo, 1999) and by the demonstration that sexual traits can reveal genetic quality (David et al, 2000;Hale et al, ms). It is also consistent with other sexual selection models (Kokko et al, 2002).…”
Section: Methodssupporting
confidence: 67%
“…There is now evidence that female subjects can gain genetic quality benefits for their offspring when they choose to mate with ornamented male subjects (Petrie, 1994;M ller and Alatalo, 1999). This makes it even more difficult to explain how genetic variance is maintained in the preferred male trait and in any fitness-determining loci that are revealed by the trait (Ritchie, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, females might choose males with a trait that, due to pleiotropy or linkage, directly indicates a gene or gene region that influences offspring fitness. While evidence for good genes effects is accumulating (Møller & Alatalo 1999), the nature of the genetic benefits indicated by male ornaments remains obscure in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic benefits in the form of good or compatible genes for the offspring are still the prominent hypothesis for why females engage in extra-pair matings [3][4][5][6] (but see [7][8][9][10] for alternative explanations such as sexual conflict). In line with this hypothesis, a growing number of studies have demonstrated that extra-pair offspring (EPO) are superior to their within-pair half-sibs in a number of fitness-related traits [11 -16].…”
Section: Introductionmentioning
confidence: 99%